Inserting Road Traffic Rules into Junior High School Curriculum to Enhance the Awareness to the Use of Road Traffic Rules - Yudhistiro Pandu Widhoyoko (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This article discusses current traffic problems. Where the awareness of the1. INTRODUCTIONThe economy in developingcountries today is improving. This isevidenced by the increasing ability ofpeople's purchasing power in somegoods. One of the impacts seen is theincreasing number of vehicles on thehighway. Which this condition thenturns up into new problems. That is acultural shock about how to transportethically and safely. What happens is,transportation and its system becomesthe main problem that should getspecial attention.This transportation problem hasmany impacts, from congestion, topollution, to the problem of accidents.In particular, in this article the focus ofthe review will be on the issue of trafficaccidents. Accident numbers should beminimized as it concerns the humansoul. According to Bellomo (2011),there are many factors causing trafficaccidents. The cause of this problem isThe 2nd International Conference on Technology, Education, and Social Science 2018 (The 2nd ICTESS 2018)road traffic user tends to disappear or is deliberately ignored. Some even causeaccidents with the consequences of death. If something is not doneimmediately, it could be that the percentage of road traffic accidents willincrease sharply. The problem is that the growth in the number of motorvehicles is not accompanied by a growing ofa good understanding of theprocedures and rules of road traffic. The worse is that, the number of theunderage children who ride vehicles have begun to increase. Thoseteenagers ride without knowing the code, the rule, the procedures, even themechanism of road traffic. And of course, they could endanger themselves andeven others. Therefore, it becomes very much important, to immediately enter thesubjects of road traffic into the Junior High School curriculum into standardsubjects, using the appropriate and relate of reference data. The subject will begiven in the grade of 3, 4, and 5 of elementary school. It will be hoped to be oneamong several solution of saving people’s life who died in vain because of theignorance in road traffic.Keywords: Road Traffic, Road Traffic awareness, Road Traffic Rules Motorcycles, JuniorHigh school curriculum.